Living environment of the early Jehol Biota: A case study from the Lower Cretaceous Dabeigou Formation, Luanping Basin (North China). (August 2021) - Qin, Zuohuan; Xi, Dangpeng; Wagreich, Michael; Sames, Benjamin; Tong, Xiaoning; Hu, Jianfang; Yu, Zhiqiang; Wan, Xiaoqiao
Abstract: The Jehol Biota of northern China provides a new and unmatched window for the reconstruction and understanding of Early Cretaceous terrestrial ecosystems. Previous studies on the paleoenvironmental and paleoclimatic background of the Jehol Biota have mainly focused on middle–late evolutionary stages while the less diverse and more narrowly distributed early Jehol Biota remains less understood. The Lower Cretaceous (Valanginian–Hauterivian) Dabeigou Formation in the Luanping Basin (North China), preserves the early stage of the Jehol Biota and can be subdivided into three members. To reconstruct the living environment of the early Jehol Biota, we explored the geochemistry, bulk mineralogy, total organic carbon, sedimentology, and paleoecology of the Dabeigou Formation from the Yushuxia section of the Luanping Basin. Decreased volcanic activity during the deposition of the Dabeigou Formation resulted in changes in its source material from felsic to mafic. The Luanping palaeolake reached its deepest water depth during deposition of the Member 2, and generally exhibited low salinity, while a short time of high salinity occurred during deposition of the Member 3. Analysis on the paleoweathering indices and other evidences, indicate that the Luanping area was generally in cold and humid climate conditions during deposition of the members 1 and 2 (correlated to the Weissert Event), but changed to warm climate conditions during deposition of the Member 3, which coincides with an increasing trend of biotic diversity. Consequently, our results suggest that the increasingly warm paleoclimate and lacustrine productivity, associated with decreasingly volcanic activity in North China, have contributed to the early evolution of the Jehol Biota. Highlights: The Lower Cretaceous Dabeigou Formation represents three depositional stages. In 1st and 2nd stages, volcanic activity was frequent and the climate was cold and humid. Cold climate in 2nd stage coincides with the cooling event during the Weissert Event. In 3rd stage, decreased volcanism and warm climate favored lacustrine productivity. Improved environmental conditions enabled the diversification of the Jehol Biota.